Comparing the Antimicrobial Actions of Greek Honeys from the Island of Lemnos and Manuka Honey from New Zealand against Clinically Important Bacteria - Gkoutzouvelidou, Maria; Panos, Georgios; Xanthou, Maria Nefertiti; Papachristoforou, Alexandros; Giaouris, Efstathios (My University, 2021)
Honey is a natural food with a long history as a traditional medicine because of its many biological characteristics, including antimicrobial, antioxidant, anti-tumor and anti-inflammatory properties. In this study, the antimicrobial actions of eight different honeys from Lemnos island (north-eastern Greece) plus manuka honey (from New Zealand, UMF 30+, licensed in many countries as topical medical preparation) were evaluated against 10 clinically relevant bacteria, including five Gram-positive and five Gram-negative. To achieve this, an agar well diffusion assay measured the diameter of inhibition zones (mm) of two selected concentrations for each honey (25% and 12.5% v/v). The minimum inhibitory and bactericidal concentrations (MIC and MBC) of each sample were also calculated and compared against two representative bacterial species (Salmonella Typhimurium and Staphylococcus aureus) using broth microdilution and agar spot methods, respectively. The pH, water activity (aw), 5-hydroxymethylfurfural (HMF) and diastase levels, together with the pollen type and content of each honey, were also determined. Results revealed that all the Lemnos honeys presented antibacterial action, which for some samples was like that of manuka. These all had an acidic pH (3.61 ± 0.04), with a aw ≤ 0.60, while it is worth noting that those found to display the strongest antibacterial actions also presented the lowest HMF content, together with the highest diastase values, both of the latter being used as quality parameters. Pollen composition of the Lemnos honeys was multifloral, underlining the rich plant biodiversity encountered on the island. To summarize, Lemnos honeys could be further exploited as natural antimicrobial systems for use in foods and medicine.
Keywords: Lemnos Greece; Antimicrobial; Bacterial pathogens; Honey; Honey quality indexes; Manuka; Melissopalynological analysis; Minimum inhibitory and bactericidal concentrations